A majority of fragile X males with methylated, full mutation alleles have significant levels of FMR1messenger RNA. Issue 7 (1st July 2001) - Tassone, F; Hagerman, R J; Taylor, A K; Hagerman, P J
Abstract : FMR1 mRNA levels were determined in peripheral blood leucocytes for 48 fragile X males with methylated, full mutation alleles that are resistant to cleavage by methylation sensitive enzymes. Using quantitative (fluorescence) RT-PCR, we observed that more than half of these males produce FMR1 mRNA, with some mRNA levels approaching those found in normal subjects. In none of the samples analysed was there any evidence of premutation alleles. These results suggest that the assumed relationship between enzyme resistance and FMR1 gene silencing may not be generally valid. Despite the presence of FMR1 mRNA in some subjects, no FMRP production was detected by either immunocytochemistry or western blotting. The low/absent FMRP levels are probably a reflection of a post-trancriptional effect such as a defect in translation.